Changes in composition and levels of hemolymph proteins during metamorphosis of Manduca sexta. (December 2020) - Cao, Xiaolong; Wang, Yang; Rogers, Janet; Hartson, Steve; Kanost, Michael R.; Jiang, Haobo
Abstract: The tobacco hornworm, Manduca sexta, is a lepidopteran model species widely used to study insect biochemical processes. Some of its larval hemolymph proteins are well studied, and a detailed proteomic analysis of larval plasma proteins became available in 2016, revealing features such as correlation with transcriptome data, formation of immune complexes, and constitution of an immune signaling system in hemolymph. It is unclear how the composition of these proteins may change in other developmental stages. In this paper, we report the proteomes of cell-free hemolymph from prepupae, pupae on day 4 and day 13, and young adults. Of the 1824 proteins identified, 907 have a signal peptide and 410 are related to immunity. Drastic changes in abundance of the storage proteins, lipophorins and vitellogenin, for instance, reflect physiological differences among prepupae, pupae, and adults. Considerably more proteins lacking signal peptide are present in the late pupae, suggesting that plasma contains relatively low concentrations of intracellular components released from remodeling tissues during metamorphosis. The defense proteins detected include 43 serine proteases and 11 serine protease homologs. Some of these proteins are members of the extracellular immune signaling network found in feeding larvae, and others may play additional roles and hence confer new features in the later life stages. In summary, the proteins and their levels revealed in this study, together with their transcriptome data, are expected to stimulate focused explorations of humoral immunity and other physiological systems in wandering larvae, pupae, and adults of M. sexta and shed light upon functional and comparative genomic research in other holometabolous insects. Graphical abstract: Image 1 Highlights: Identification of 1828 proteins in hemolymph of Manduca sexta in four different life stages Elucidation of the major functions of insect hemolymph, i.e. storage, transport, and immunity Detection of stage-specific proteomic changes by expression profiling and GO enrichment Examination of developmental changes in mRNA and protein levels of immunity-related genes